2021
DOI: 10.1002/bin.1825
|View full text |Cite
|
Sign up to set email alerts
|

Teaching generalized question‐discrimination skills to children with autism: Conceptual and applied considerations

Abstract: Neuro‐typically developing children demonstrate accurate, discriminated responding to a variety of questions in the presence of nonverbal stimuli. For children diagnosed with autism, however, such question discrimination skills can be significantly impaired. An error frequently observed in clinical practice is that of the child who, despite previous mastery of the relevant color tacts, says “Ball” when presented with a blue ball and the question “What color?” This paper explores the role of multiple verbal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is also possible that the participants’ histories with instructional stimuli affected responding during probes (degli Espinosa, 2021 ). We did not assess whether the participants could respond as a speaker or a listener to the features before IF.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the participants’ histories with instructional stimuli affected responding during probes (degli Espinosa, 2021 ). We did not assess whether the participants could respond as a speaker or a listener to the features before IF.…”
Section: Discussionmentioning
confidence: 99%
“…When the component skills were insufficient to facilitate the emergence of intraverbal tacts, we evaluated the effects of two variations of a procedure directed at enhancing both the divergent control exerted by the auditory stimulus and the discriminability of joint control. Although other studies have suggested similar conceptualizations of the function of repeating the critical term in a question with the answer insofar as its role in enhancing intraverbal control (e.g., "color red";degli Espinosa, 2022;degli Espinosa et al, 2020degli Espinosa et al, , 2021, to date no study has isolated the effects of a divergent intraverbal response or separated these effects from, for example, the effects of ensuring attending to the keyword in the question.…”
mentioning
confidence: 99%
“…"the overlapping topography between the tact ("green" evoked by the visual property of the ball) and intraverbal ("green" evoked by the auditory stimulus "color"). Thus, this response may be considered an intraverbal tact (or intraverbally controlled tact; Bondy et al, 2004;degli Espinosa, 2021).…”
mentioning
confidence: 99%